2022
DOI: 10.33365/jtk.v16i1.1857
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Kualitas Layanan Electronic Pendapatan Asli Daerah (E-PAD) Di Kabupaten Banyuwangi Menggunakan Metode E-GovQual dan Importance Performance Analysis

Abstract: Pemerintah Kabupaten Banyuwangi pada tahun 2018 telah menciptakan sebuah inovasi baru dalam pengembangan e-Government salah satunya yaitu electronic Pendapatan Asli Daerah (E-PAD) yang berbasis website beralamatkan https://layanan.banyuwangikab.go.id. Layanan E-PAD merupakan sebuah inovasi milik Pemerintah Kabupaten Banyuwangi yang dikelola oleh Badan Pendapatan Daerah Kabupaten Banyuwangi. E-PAD merupakan layanan yang dapat membantu dalam menyampaikan informasi dan memberikan pelayanan kepada seluruh wajib pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…The development of E-GovQual measurement in Indonesian local governments requires further attention, particularly in the context of the E-Government system in the West Java province. This research, grounded in behavioral theory, has successfully demonstrated that variables such as usability, credibility, functionality of interaction, dependence, content and information presentation, and support have a significant impact on the quality of local government (Septrisulviani et al, 2017;Purnama & Reyta, 2023;Prasetyo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The development of E-GovQual measurement in Indonesian local governments requires further attention, particularly in the context of the E-Government system in the West Java province. This research, grounded in behavioral theory, has successfully demonstrated that variables such as usability, credibility, functionality of interaction, dependence, content and information presentation, and support have a significant impact on the quality of local government (Septrisulviani et al, 2017;Purnama & Reyta, 2023;Prasetyo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The second study was conducted by (Jayanti et al, 2022) with the title "Evaluation of the Implementation of E-Government Public Service Content Complaints Using E-GovQual, Importance Performance Analysis and Heuristic Evaluation (Case Study: Ministry of Communication and Information, APTIKA Directorate) [15]. The third research is a study conducted by Prasetyo et al, with the title "Evaluation of the Quality of Regional Native Income Electronic Services (E-PAD) in Banyuwangi Regency Using the E-GovQual and IPA Methods" [16].…”
Section: Research Methods 21 Previous Researchmentioning
confidence: 99%
“…Penelitian Purwanto & Sugiarto [7][8] [9], Kesehatan merupakan aspek yang sangat penting bagi manusia, karena tanpa kesehatan yang baik, mereka akan kesulitan menjalankan aktivitas. Pemerintah menyediakan lembaga pelayanan kesehatan berdasarkan klaster, dari Pusat Pembantu Kesehatan (PusTu) hingga Rumah Sakit Rujukan (Type C, B, dan A).…”
Section: Tinjauan Literaturunclassified